How Can We Decrease Early Dialysis Initiation? An Interactive Quality Improvement Teaching Case for Health Care Providers and Narrative Review of Quality Improvement Methodology - Khaled Lotfy; Epsita Shome-Vasanthan; Samuel A. Silver; Tamara Glavinovic (Canadian Journal of Kidney Health and Disease)
Purpose of Review: Quality improvement (QI) initiatives use a team-based approach to problem-solving clinical and health system issues. All QI initiatives require the coordinated efforts of health care professionals and other stakeholders to encourage the provision of evidence-based clinical care. Most clinicians understand the principles of QI but may lack the training necessary to undertake individual projects. Methods: An educational, nephrology-oriented clinical case was created based on the IDEAL study on timing of dialysis initiation, a prioritized quality indicator in several provinces. The case illustrates how to utilize commonly employed QI methodology and to provide a pragmatic framework for both developing and running a QI project. Core concepts addressed in this review include how to perform a QI chart audit, identification of a quality-of-care problem, engaging stakeholders, and how to conduct a root cause analysis that leads to selection of QI measures and change solutions. Last, plan-do-study-act (PDSA) cycles and interpretation of data using run charts are highlighted. Sources of Information: PubMed and Google scholar were used as sources of published QI methodology. Key Findings: This nephrology-oriented QI case highlights how a core set of QI principles and tools can be used to improve clinical care. This review demonstrates that determining clear goals, utilizing evidence-based guidance to improve timing of dialysis initiation, engaging the appropriate stakeholders, identifying a feasible and measurable change, and tracking if that change leads to improvement are essential components of all QI initiatives. The above framework can be utilized in a variety of clinical areas both within and beyond nephrology-specific care. Limitations: Considerations regarding QI-specific data analysis were not addressed as they were beyond the scope of this review.